Body Temperature Control Using a Robotic Arm - Varela-Aldás, José (2021)
At the end of 2019, a highly contagious virus appears, changing the form of interaction between humans, this has implied the use of technology as a support tool to counteract the effects of the new disease (COVID-19). Although many technologies have been successfully adapted, applied robotics promises to reduce or even eliminate the need for person-to-person contact. This article presents the control of the body temperature of the clients of a commercial premises through the implementation of a system that includes a robotic arm, two sensors and a mobile device. The robotic arm is constructed using 3D printing and a low-cost electronic circuitry, body temperature is obtained using an infrared sensor, and a mobile device displays, alerts, and stores the information. The developed code allows remote control of the robot positions or a pre-programmed sequence is automatically activated that includes temperature measurement and hand disinfection. The results show the robot in operation and the data acquired by the system, observing adequate temperatures in most of the users and a single alert during the tests carried out. The conclusions establish the importance of the system in the real application and highlight the multiple benefits of this proposal.